The effects of relocation and level of affectedness on mood and anxiety symptom treatments after the 2011 Christchurch earthquake. (March 2016) - Hogg, Daniel; Kingham, Simon; Wilson, Thomas M.; Ardagh, Michael
Abstract: In this longitudinal study, we compare the effects of different types of relocation and level of affectedness on the incidence and relapse of mood and anxiety symptom treatments identified by publicly funded care or treatment one year before and one and two years after the '2011 Christchurch earthquake' in New Zealand. Based on a subset of Christchurch residents from differently affected areas of the city identified by area-wide geotechnical land assessments (no to severe land damage) 'stayers', 'within-city movers', 'out-of-city movers' and 'returners' were identified to assess the interaction effect of different levels of affectedness and relocation on the incidence and relapse of mood and anxiety symptom treatments over time. Health and sample information were drawn from the New Zealand Ministry of Health's administrative databases allowing us to do a comparison of the pre-/post-disaster treatment status and follow-up on a large study sample. Moving within the city and returning have been identified as general risk factors for receiving care or treatment for mood or anxiety symptoms. In the context of the 2011 Christchurch earthquake, moving within the city showed a protective effect over time, whereas returning was a significant risk factor in the first post-disaster year. Additionally, out-of-city movers from minor, moderately or severely damaged Christchurch's plain areas were identified as especially vulnerable two years post-disaster. Generally, no dose-response relationship between level of affectedness and mood or anxiety symptom treatments was identified, but the finding that similarly affected groups from the city's plain areas and the more affluent Port Hills showed different temporal treatment trends highlights the importance of including socio-economic status in exposure assessment. High-risk groups included females, older adults and those with a pre-existing mental illness. Consequently, mental health intervention programs should target these vulnerable groups, as well as out-of-city movers from affected areas in the long run. Highlights: Different mobility types can have different post-disaster impacts on mental health. Moving within the city showed a protective effect on mood/anxiety over time. Temporary relocation was identified as a short-term risk factor. Moving out of the city from less affluent affected areas was a long-term risk factor. No clear post-disaster dose-response relationship could be confirmed.